Effects of Nanomaterials on the Body Composition of Patients with Dyslipidemia Based on Different Strength Sports Equipment - Xiang Liu; Guoquan Ma (Journal of Chemistry)
Relevant studies have shown that the use of sports equipment for exercise can regulate the body composition of patients, thereby achieving the purpose of improving the metabolism of blood lipids in the body. Based on this, this article takes patients with dyslipidemia as the research object and explores the changes in their body composition and shape using different strength sports equipment made of nanomaterials during sports rehabilitation training. In this study, 200 patients with dyslipidemia were selected as experimental subjects in the form of interviews and questionnaires. According to the type of exercise, they were divided into 56 men in the men’s running group, 56 men in the men’s spinning group, 44 women in the women’s running group, and 44 women in the women’s spinning group. 12 weeks of incremental exercise training were carried out. The results of the experiment found that after the end of the 12-week exercise training, the body composition of the subjects in each group changed significantly (P<0.05). The changes in the male and female spinning group were more obvious than those in the running group, and the weight of the male spinning group, waist circumference, and hip circumference decreased by 2.3%, 3%, and 3.5% and those of women’s spinning group decreased by 3.1%, 3.4%, and 3.9%. In addition, blood lipids in each group also changed significantly (P<0.05); there is a significant statistical difference. Through a return visit two years after the end of the experiment, it was found that most of the subjects had symptoms of discomfort, indicating that the nanomaterials have a certain negative impact on the human body.